2021
DOI: 10.1093/plphys/kiab349
|View full text |Cite
|
Sign up to set email alerts
|

Imaging plant cells and organs with light-sheet and super-resolution microscopy

Abstract: The documentation of plant growth and development requires integrative and scalable approaches to investigate and spatiotemporally resolve various dynamic processes at different levels of plant body organization. The present update deals with vigorous developments in mesoscopy, microscopy and nanoscopy methods that have been translated to imaging of plant subcellular compartments, cells, tissues and organs over the past 3 years with the aim to report recent applications and reasonable expectations from current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 113 publications
(133 reference statements)
0
27
0
Order By: Relevance
“…We have recently established light-sheet fluorescence microscopy for the spatiotemporal imaging of plant development at subcellular, cellular, tissue and organ levels under controlled environmental conditions (Ovečka et al ., 2018). It was utilized in alfalfa for the characterization of root development (Vyplelová et al ., 2018) and the involvement of actin cytoskeleton in the interaction with S. meliloti (Ovečka et al ., 2022). Live-cell imaging using LSFM clearly showed relocation of SIMK from root hair tips to the S. meliloti docking site and further close association with sites of rhizobia internalization.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently established light-sheet fluorescence microscopy for the spatiotemporal imaging of plant development at subcellular, cellular, tissue and organ levels under controlled environmental conditions (Ovečka et al ., 2018). It was utilized in alfalfa for the characterization of root development (Vyplelová et al ., 2018) and the involvement of actin cytoskeleton in the interaction with S. meliloti (Ovečka et al ., 2022). Live-cell imaging using LSFM clearly showed relocation of SIMK from root hair tips to the S. meliloti docking site and further close association with sites of rhizobia internalization.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Vernet et al successfully observed the nematode–root interactions in tomato using light sheet fluorescence microscopy (LSFM) and optical projection tomography (OPT) [ 117 ]. Moreover, simultaneous imaging of S. meliloti (magenta) and the host cytoskeleton in cytoskeletal marker gene transgenic alfalfa plants was realized by using light-sheet and super-resolution microscopy, providing an approach to track the dynamic changes in the host cytoskeleton and pathogenic microbes over a long time at the super-resolution level [ 118 ].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Advanced imaging technologies, such as Lattice Light Sheet (LLS) microscopy, enables long term 4D imaging without photobleaching [109] which has been used to analyse mitotic cells in mammalian cells [110] and is a promising approach for plants. Further, Light Sheet [111] and vertical imaging [112] are gaining more traction in plants and can provide cell division patterns that take the effect of gravity into account. Structured illumination microscopy has been instrumental to better understand CESA dynamics at the PM [113].…”
Section: Challenges and Emerging Technologiesmentioning
confidence: 99%